Peranan Gembala Sidang Dalam Pertumbuhan Iman Kaum Muda - Despri Despri; Yahya Usat (Sekolah Tinggi Teologi Tenggarong, 2020)
The shepherd has a duty that must be accountable to God. The pastor is a leader who guides and guides the church so that the church experiences faith growth. In this effort the pastor needs to teach the stages of achieving it, and provide a correct understanding of faith. Thus the shepherd must play a full role in shepherding. The pastor's leadership is leadership based on the love of Christ not based on intimidation and oppression. Shepherds must be careful in applying the principles of leadership not to get caught up in the principles of secular leadership. Thus this study aims to examine the role of the pastor in the growth of the faith of young people. This research was conducted at the Indonesian Gospel Camp Long Pejeng Church, East Kutai Regency, East Kalimantan Province.Gembala memiliki tugas yang harus dipertangungjawabkan kepada Allah. Gembala pemimpin yang membimbing dan menuntun jemaat agar jemaat mengalami pertumbuhan iman. Dalam upaya tersebut gembala perlu mengajarakan tahap-tahap mencapainya, dan memberi pemahaman yang benar tentang iman. Sehingga gembala sidang harus bermain penuh dalam penggembalaan. Kepemimpinan gembala merupkan kemimpinan yang berdasar atas kasih Kristus bukan berdasarkan pada pengintimidasian dan penindasan. Gembala harus berhati-hati dalam menerapkan prinsip-prinsip kepemimpinan jangan sampai terjebak dalam prinsip-prinsip kepemimpinan sekuler. Dengan demikian penelitian ini bertujuan untuk menguji sidang gembala sidang dalam pertumbuhan iman muda. Penelitian ini dilaksanakan di Gereja Kemah Injil Indonesia Long Pejeng, Kabupaten Kutai Timur.